PYTHON AS A CHAT-BOT DEVELOPMENT TOOL - Salihova Venera Karimjanovna (Galaxy International Interdisciplinary Research Journal, 2023)
Constantly changing market conditions, high speed of decision-making, multitasking in asset management and the need to reduce risks require modern approaches to business organization. The solution to the increasingly complex internal and external environment of the enterprise lies in the integrated automation of business processes.